Drug-induced visceral angioedema - Prashanth M. Thalanayar; Ibrahim Ghobrial; Fritz Lubin; Reena Karnik; Robin Bhasin (Greater Baltimore Medical Center, 2014)
Angioedema associated with angiotensin converting enzyme inhibitors (ACEIs) is due to the accumulation of bradykinin and its metabolites. Angiotensin receptor blockers (ARBs) produce anti-hypertensive effects by blocking the angiotensin II AT1 receptor action; hence bradykinin-related side effects are not expected. However, we notice the occurrence of ARB-induced angioedema as not a very rare side effect. Visceral drug-induced angioedema has been reported with ACEIs, not with ARBs. This underlying review will help educate readers on the pathophysiology and recent guidelines pertaining to ACEI- and ARB-induced visceral angioedema.